The Effect of Transformational Leadership and Organizational Culture on Employee Performance Moderated Organizational Commitment - Diansyah Diansyah; Fella Attaqi Putri (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study is to provide recommendations to companies on Transformational Leadership to improve employee performance. The research method used is Structural Equation Modeling (SEM), the data analysis tool used is Partial Least Square (PLS). The population in this study were all workers in as many as 100 respondents. It is very important to instill the attitude of Transformational Leadership and Organizational Culture in a company because seeing its large role directly affects Organizational Commitment and is able to moderate the influence of the independent variables of Transformational Leadership, Organizational Culture on the dependent variable, namely Employee Performance and Organizational Commitment.